The enhanced magnetocaloric effect in Dy2In1−xAlx by a non-hysteresis metamagnetic phase transition. (1st July 2019) - Yao, Guiquan; Wei, Fulong; Zhang, Jinsong; Fan, Xiaomeng; Yin, Xiaowei; Cui, Weibin; Wang, Qiang
Abstract: To enhance the magnetocaloric effect of the second-order magnetic phase transition is eagerly sought in the development of practical magnetic refrigeration technology. Here, demonstrated by Dy2 In1− x Al x (0 ≤ x ≤ 0.5) system, the max magnetic entropy change is significantly enhanced to 13.4 Jkg −1 K −1 in Dy2 In0.7 Al0.3 and 10.8 Jkg −1 K −1 in Dy2 In0.6 Al0.4 alloys compared with 8.8 Jkg −1 K −1 in Dy2 In through a field-induced metamagnetic phase transition, which is unconventionally of nonhysteresis confirmed by magnetic measurements. Considering that nonhysteresis metamagnetic transition occurs at the critical composition where hexagonal structure is formed for x ≤ 0.3 while orthorhombic structure for x ≥ 0.4, the origin is ascribed to the lattice distortion. Graphical abstract: Unlabelled Image